Fusion Research in Ioffe Institute. (29th July 2015) - Askinazi, L.G.; Afanasyev, V.I.; Altukhov, A.B.; Bakharev, N.N.; Belokurov, A.A.; Bulanin, V.V.; Bykov, A.S.; Chernyshev, F.V.; Chugunov, I.; Dyachenko, V.V.; Esipov, L.A.; Gin, D.; et al.
Abstract: In this paper we present the fusion related activities of the Plasma Physics Division at the Ioffe Institute. The first experiments on lower hybrid current drive (LHCD) in a spherical tokamak performed at the Globus-M tokamak ( R = 0.36 m, a = 0.24 m, B t = 0.4 T, I p = 200 kA) with a novel poloidally oriented grill resulted in an RF driven current of up to 30 kA at (100 kW, 2.5 GHz), exceeding the modelling predictions. At the FT-2 tokamak ( R = 0.56 m, a = 0.08 m, B t = 3 T, I p = 30 kA) experiments with a traditional toroidally oriented grill revealed no strong dependence of the LHCD density limit on the H / D ratio in spite of LH resonance densities differing by a factor of 3. Microwave Doppler reflectometry (DR) at the Globus-M, and DR and heavy ion beam probe measurements at the tokamak TUMAN-3M ( R = 0.53 m, a = 0.24 m, B t = 1.0 T, I p = 190 kA) demonstrated geodesic acoustic mode (GAM) suppression at the L to H transition. Observations at FT-2 using Doppler Enhanced Scattering showed that the GAM amplitude is anti-correlated both spatially and temporally to the drift turbulence level and electron thermal diffusivity. For the first time turbulence amplitude modulation at the GAM frequency was found both experimentally and in global gyrokinetic modelling. A model of the L–H transition is proposed based on this effect. The loss mechanisms of energetic ions' (EI) were investigated in the neutral beam injection (NBI) experiments on Globus-M and TUMAN-3M. Empirical scaling of the 2.45 MeV DD neutron rate for the two devices shows a strong dependence on toroidal field and plasma current justifying the B t and I p increase by a factor of 2.5 for the proposed upgrade of Globus-M. Bursts of ∼1 MHz Alfvenic type oscillations correlating with sawtooth crashes were observed in ohmic TUMAN-3M discharges. The possibility of low threshold parametric excitation of Bernstein and upper hybrid waves trapped in drift-wave eddies resulting in anomalous absorption in electron cyclotron resonance heating (ECRH) experiments in toroidal plasmas was identified theoretically. A novel method of radial correlation Doppler reflectometry is shown to be capable of measuring the turbulence wave-number spectrum in realistic 2D geometry. On the progress in design and fabrication of three diagnostics for ITER developed in the Ioffe institute is reported: neutral particle analysis, divertor Thomson scattering and gamma spectroscopy.